IMPLEMENTASI KEGIATAN MEMBACA 15 MENIT SEBAGAI UPAYA PENGUATAN BUDAYA LITERASI DAN MINAT BACA SISWA: STUDI PUSTAKA - Khalishah Khair, Hanifah; Andra, Vebbi; Friantary, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low reading interest and literacy skills of students in Indonesia are a serious challenge in contemporary education. As a structural solution, the Government launched the School Literacy Movement (GLS), one of whose main pillars is a 15-minute reading program before class begins. This study aims to analyze the implementation, effectiveness, obstacles, and impact of the 15-minute reading activity on strengthening students' literacy culture and reading interest based on a literature review. The research method used is a literature review by collecting, reducing, analyzing, and synthesizing relevant scientific journal articles from the Google Scholar database. The results of the study indicate that the consistent implementation of 15-minute reading is able to stimulate reading habits, improve vocabulary mastery, and foster students' intrinsic reading interest. However, the success of this program is greatly influenced by the availability of varied reading books (non-textbooks), the active role of teachers as role models, and the creation of a literacy-rich school environment (literate environment). The main obstacles found include student boredom due to monotonous post-reading activities and limited reading corner facilities. This study concludes that the 15-minute reading activity effectively becomes the foundation of a school literacy culture if supported by adaptive and collaborative program management.